Effect of dietary supplementation of crude microalgal extracts on growth performance, survival and disease resistance of Lates calcarifer (Bloch, 1790) larvae - Gora, Adnan Hussain; Ambasankar, K.; Sandeep, K. P.; Rehman, Saima; Agarwal, Deepak; Ahmad, Irshad; Ramachandran, Kasilingam (Indian Journal of Fisheries, 2019)
The present study aimed to assess growth performance and health status of Lates calcarifer larvae fed with crude microalgal extracts. Larvae weighing 5.96 ± 0.39 mg were randomly divided into four experimental groups in triplicates, with each replicate having 35 larvae. Four diets formulated to contain 55% protein and 12% lipid, were prepared with pigment rich microalgal extracts at 0% (T1) and 1% each of crude phycocyanin (T2), chlorophyll (T3) and astaxanthin (T4) extracts. The experiment was carried out in 30 l plastic tanks by feeding experimental diets to satiation. There was no significant difference (p<0.05) in growth performance in larval groups fed different experimental diets. Percentage survival during the feeding experiment was significantly higher in the astaxanthin fed group (77.14±1.65) and lower in chlorophyll fed group (36.19±0.95) compared to control group. Cannibalism (%) was significantly reduced in the treatments fed astaxanthin (7.61±0.95) and phycocyanin (8.57±0.3) pigmented diets compared to chlorophyll fed group (13.33±0.95) and control group. Bacterial challenge with pathogenic Vibrio alginolyticus revealed highest resistance in astaxanthin and phycocyanin fed larvae. The study confirms that astaxanthin and phycocyanin at 1% dietary levels improve survival and disease resistance in Asian seabass larvae but do not affect growth performance.